Curcumin Reverses the Scopolomine-induced Cognitive Impairment by iNOS and Acetylcholinesterase Inhibition in Rodent Model of Schizophrenia (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Schizophrenia is a severe neuro-developmental psychiatric disorder. Curcumin is a polyphenolic compound extracted from turmeric. It is known for its antioxidant, anti-inflammatory, neuroprotective, and precognitive properties. The purpose of the current study was to evaluate the role of curcumin in scopolamine induced cognitive impairment in animal model of schizophrenia. The elevated plus-maze test was utilised to study the curcumin effect on learning and memory. Curcumin (100 mg/kg, i.p.) was administered daily for 28 days in animals. Behavioural tests such as transfer latency (TL) and spontaneous alteration behaviour was assessed after the last dose of curcumin on the 28th day, followed by biochemical estimations. Present study reported that curcumin showed anti-amnesic effect in animal models of cognitive impairment of schizophrenia. Curcumin reduced the TL compared to toxic control group (scopolamine per se) (P <0.001) in elevated plus maze. In spontaneous alteration behaviour test, curcumin significantly increased percentage alteration and possible alteration as compared to toxic control group (P <0.001). A significant change in acetyl cholinesterase activity, nitrate and oxidative parameters was observed, thus, confirming its anti acetyl cholinesterase, NOS (nitric oxide synthase) inhibition and antioxidant properties (P <0.05). The present study put forward the claim of curcumin as a new and safer therapeutic alternative for the treatment of cognitive impairment in Schizophrenia. The underlying mechanism of this potential effect may be related to anticholinesterase and nitric oxide synthase inhibition activity of curcumin. Further research is warranted for confirming the suggested pathways accountable for memory alleviating effects of curcumin in Schizophrenia.